Traditional uses, botany, phytochemistry, pharmacology, separation and analysis technologies of Euonymus alatus (Thunb.) Siebold: A comprehensive review. (15th September 2020) - Fan, Linhong; Zhang, Chunling; Ai, Li; Wang, Li; Li, Lin; Fan, Wenxiang; Li, Ruolan; He, Liying; Wu, Chunjie; Huang, Yongliang
Abstract: Ethnopharmacological relevance: Euonymus alatus (Thunb.) Siebold ( E. alatus ), a well-known medicinal plant, has been widely used thousands of years in China for the treatment of various diseases such as urticaria, dysmenorrhea, wound, dysentery, blood stasis, rheumatism and arthritis. Due to the extensive application of E. alatus in the fields of ethnopharmacological usage, the pharmaceutical researches of E. alatus keeps deepening. Aim of the study: This paper reviewed and summarized the integrated research progress of this medicinal plant. A comprehensive summary and comparison of traditional usages, botany, phytochemistry, pharmacology, toxicology, separation and analysis technologies of the E. alatus highlight recent scientific advances, which provides new insights into the research and development of this medicinal plant and would be helpful to promote the research situation of underlying pharmacological mechanisms and further utilizations of E. alatus . Material and methods: Literature survey was carried out via classic books of herbal medicine, PhD. and MSc. Dissertations. Online scientific databases including Pubmed, SciFinder, Science Direct, Scopus, the Web of Science, Google Scholar, China National Knowledge Infrastructure (CNKI) and others were searched up to February 2020 to identify eligible studies. All literatures of the research subject are analyzed and summarized in this review. Results: The E. alatus has been widely used in traditional practice in China, Korea and other Asian Countries. In the study of phytochemistry, more than 230 chemical constituents have been isolated and identified from E. alatus, including sesquiterpenoids, diterpenoids, triterpenoids, flavonoids, phenylpropanoids, lignans, steroids, alkaloids and other compounds. Among them, literature reports show that flavonoids and steroids are the most important bioactive substances found in this plant. A number of researches also have shown that extracts and compounds from E. alatus exert a wide spectrum of pharmacological effects, including antidiabetic effect, anti-tumor effects, anti-inflammatory effects, hepatoprotective effects, antioxidant effects, antibacterial effects, as well as other effects. However, most of the studies without clinical research. Research into plant's toxicological effects has also been limited. In addition, this review also summarizes and compares the separation and analysis technologies of E. alatus . Conclusions: E. alatus has potential for the treatment of many diseases, especially tumors and diabetes. But many traditional uses of E. alatus have not been validated by current investigations. Additionally, modern studies haven't gone far enough into its pharmacological effects and the corresponding chemical constituents, more efforts should be made to illuminate the underlying mechanisms of E. alatus for treatment of tumors and diabetes. Moreover, the toxicological effects of this plant can be further studied. Currently, there are limited studies on its side effects and toxicological effects, which should provide further guidance for the safety of clinical use. Graphical abstract: Image 1